CO2 utilization in the perspective of industrial ecology, an overview. (December 2015) - Meylan, Frédéric D.; Moreau, Vincent; Erkman, Suren
Graphical abstract: Highlights: Suitable CO2 capture and utilization pathways are identified. They are assessed in the perspective of industrial ecology. Synergies between processes bring material and energy saving opportunities. Future prospects and potential limitations are highlighted. Abstract: Carbon dioxide emissions from anthropic activities have accumulated in the atmosphere in excess of 800 Gigatons since preindustrial times, and are continuously increasing. Among other strategies, CO2 capture and storage is one option to mitigate the emissions from large point sources. In addition, carbon dioxide extraction from ambient air is assessed to reduce the atmospheric concentration of CO2 . Both direct and indirect (through photosynthesis) pathways are possible. Geological sequestration has significant disadvantages (high cost, low public acceptance, long term uncertainty) whereas carbon dioxide recycling (or utilization) is more consistent with the basic principle of industrial ecology, almost closing material cycles. In this article, a series of technologies for CO2 capture and valorization is described as integrated and optimized pathways. This integration increases the environmental and economic benefits of each technology. Depending on the source of carbon dioxide, appropriate capture and valorization processes are evaluated based on material and energy constraints.